2017
DOI: 10.3390/ma10040393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Thermal Stability of Acetylated Slicewood Production by Alkali-Catalyzed Esterification

Abstract: This study was compared and characterized two different alkali (potassium carbonate (PC) and potassium acetate (PA))-catalyzed acetylations of slicewood with vinyl acetate (VA) by a vapor phase reaction. The results revealed that the esterification reaction between VA and the hydroxyl groups of slicewood could be improved by using PC or PA as a catalyst. Additionally, a significant weight percent gain was obtained after VA acetylation with 5% of catalyst. Furthermore, the reactivity of the cellulose hydroxyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As shown in Table 3 , the E a at 10% conversion of various lignocellulosic materials increase in order of Taiwan red pine (146–161 kJ/mol), makino bamboo (158–175 kJ/mol), India-charcoal trema (185–194 kJ/mol) and Chinese fir (194–202 kJ/mol). The E a is defined as the minimum energy that must be overcome to start a chemical reaction [ 27 ]. As the E a value increases, the minimum energy required to start thermal decomposition also increases.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 3 , the E a at 10% conversion of various lignocellulosic materials increase in order of Taiwan red pine (146–161 kJ/mol), makino bamboo (158–175 kJ/mol), India-charcoal trema (185–194 kJ/mol) and Chinese fir (194–202 kJ/mol). The E a is defined as the minimum energy that must be overcome to start a chemical reaction [ 27 ]. As the E a value increases, the minimum energy required to start thermal decomposition also increases.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the initial blocking of the hydroxyl end group blocks to some extent the second degradation process (Persenaire et al, 2001). Works with other polymers also showed that their acetylation lead to an increase of the thermal stability of the modified polymer (Hung et al, 2017;Yang et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…The average E a of BF/WF/HDPE composites increased to 204.6 kJ/mol after the fiber loading level increased to 6.7 wt.%. E a is a key factor used to ascertain the reaction rate, indicative of the minimum energy necessary to reach an activating molecule from the reactant molecule in the chemical reaction [42]. Different reactions are matched with different activation energies.…”
Section: Kinetics Of Wpc Reinforced With Bfsmentioning
confidence: 99%